Medication and symptom severity in schizophrenia patients in COVID-19 pandemic: A cross-sectional study - Kılıçaslan, Aslı Kazğan; Yildiz, Sevler; Kurt, Osman; Korkmaz, Sevda (My University, 2021)
The present study aimed to determine the possible correlation between medical treatment [oral antipsychotics (OAP), long-acting injectable antipsychotics (LAI), oral + long-acting injectable antipsychotics (OAP + LAI)] and symptom severity, and the compliance of schizophrenia patients with the medication during the COVID-19 pan- demic. The study was conducted with 100 schizophrenia patients who applied to the psychiatry outpatient clinic during the pandemic and met the study criteria. Sociode- mographic data form, Positive and Negative Symptom Scale (PANSS), and Functional Recovery Scale in Schizophrenia (FRSS) were applied to each participant. The rate of patients who quit current treatment was 19%. A statistically significant difference was determined between the patients on OAP and those on LAI, and between those on OAP and those on OAP + LAI based on the overall scale scores (p <0.001). There were significant differences between the FRSS scores of the patients who discontinued treatment, those who continued medication, and those who switched to depot antipsychotic medication (p <0.001). There was a significant difference between those who discontinued medication and those who continued medication based on the overall scale scores (p <0.001). In the present study, it was determined that the symptoms of patients on only LAI medication and those in OAP + LAI medication were lower, and their functionality scores were higher when compared to the patients on only OAP medication. It was also determined that among the schizophrenia patients who applied to psychiatry clinic during pandemic, those who were on LAI exhibited better func- tionality and lower symptom burden when compared to other treatment modalities. During the pandemic, it was observed that LAI medication protected the patients better.
Keywords: COVID-19 pandemic; Schizophrenia; long-acting injectable antipsychotics; oral antipsychotics